On the Sharp Regularity for Arbitrary Actions of Nilpotent Groups on the Interval: The Case of n4 - Navas-Flores, A; Rivas-Espinosa, C (Cambridge University Press, 2018)
In this work, we determine the largest for which the nilpotent group of four-by-four triangular matrices with integer coefficients and the value one in the diagonal embeds into the group of diffeomorphisms of the closed interval. © Cambridge University Press, 2016.